Uniqueness of solutions of impulsive hyperbolic differential-functional equations - Janiszewska-Walczak, D. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For impulsive partial differential-functional equations, we prove the theorems on existence and uniqueness of solutions and their continuous dependence on the right-hand sides of the equations.